2016
DOI: 10.4292/wjgpt.v7.i2.227
|View full text |Cite
|
Sign up to set email alerts
|

Update on management of Barrett's esophagus

Abstract: develops as a consequence of gastroesophageal reflux disease. The significance of Barrett's metaplasia is that predisposes to cancer development. This article provides a current evidence-based review for the management of BE and related early neoplasia. Controversial issues that impact the management of patients with BE, including definition, screening, clinical aspects, diagnosis, surveillance, and management of dysplasia and early cancer have been assessed. Core tip: Barrett's esophagus (BE) is a common cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…The present study shows that the overall five‐year survival rates of esophageal cancer have increased in the examined study period. We believe that this is not only due to the improvement in surgical techniques and adjuvant therapy, but also due to the early diagnosis of an increased number of esophageal cancer cases owing to the increasing use of upper gastrointestinal endoscopy . Interestingly, the five‐year survival rates for EAC were higher compared to ESCC, especially after 1992, which is consistent with the previous studies .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study shows that the overall five‐year survival rates of esophageal cancer have increased in the examined study period. We believe that this is not only due to the improvement in surgical techniques and adjuvant therapy, but also due to the early diagnosis of an increased number of esophageal cancer cases owing to the increasing use of upper gastrointestinal endoscopy . Interestingly, the five‐year survival rates for EAC were higher compared to ESCC, especially after 1992, which is consistent with the previous studies .…”
Section: Discussionsupporting
confidence: 88%
“…This increasing prevalence of BE is likely to result in the increasing rates of EAC in the next few decades. Consequently, the strategy for the prevention and control of EAC relies on upper endoscopy coupled with biopsy to identify BE in patients with GERD and regular endoscopic surveillance in BE patients …”
Section: Discussionmentioning
confidence: 99%
“…Although recent analysis of SEER data showed that 5-year survival rates for all age patients with esophageal cancer increased from 1973 to 2010 (for both localized and regional stages), information on survival among older patients remains sparse [ 51 ]. It has been speculated that survival of patients with esophageal cancer was slowly improving due to better surgical techniques, adjuvant therapy, and increasing use of upper gastrointestinal endoscopy for early diagnosis [ 51 , 52 ]. However, it seems that this may not be the case for older patients for whom a deceleration in survival could be associated with changing patterns of histotype-specific incidence with esophageal adenocarcinoma rates surpassing the rates of squamous cell carcinoma [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no statistical significance between the groups. It is important remember: clinical or surgical treatment does not suspend the obligatory surveillance for the transformation of BE into adenocarcinoma with endoscopy [ [13], [14]]. This surveillance is valid only for patients diagnosed with BE, patients with GERD have no indication of endoscopic surveillance unless there are other warning signs or risk factors for Barrett's esophagus [ [15], 16].…”
Section: Discussionmentioning
confidence: 99%